2016
DOI: 10.1111/ajt.13637
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Heart Transplant Recipients With Previous Neoplasia History

Abstract: Neoplasm history increases morbidity and mortality after solid organ transplantation and has disqualified patients from transplantation. Studies are needed to identify factors to be considered when deciding on the suitability of a patient with previous tumor for heart transplantation. A retrospective epidemiological study was conducted in heart transplant (HT) recipients (Spanish Post-Heart Transplant Tumor Registry) comparing the epidemiological data, immunosuppressive treatments and incidence of post-HT tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Other demographic and comorbid conditions were less important or not significant [10]. Another series could not identify PTM as predictor, even not after adjustment for gender and era, although male gender and era before 1993 were predictive [11]. In a pediatric series of patients with CCMP, listing in earlier era, need for a ventricular assist device and female gender were predictors for mortality after OHT, but CCMP was not [8].…”
Section: Mortalitymentioning
confidence: 84%
See 4 more Smart Citations
“…Other demographic and comorbid conditions were less important or not significant [10]. Another series could not identify PTM as predictor, even not after adjustment for gender and era, although male gender and era before 1993 were predictive [11]. In a pediatric series of patients with CCMP, listing in earlier era, need for a ventricular assist device and female gender were predictors for mortality after OHT, but CCMP was not [8].…”
Section: Mortalitymentioning
confidence: 84%
“…However, the series investigating the effect of hematologic PTM on posttransplant outcome separately showed that this type of PTM resulted in a significantly worse post-transplant survival and this effect was larger than any demographic or comorbid factor, except for new onset dialysis [10]. Only in one series, patients with PTM had a decreased survival, but this became only evident after 5 years, and only in a univariate analysis [11].…”
Section: Mortalitymentioning
confidence: 97%
See 3 more Smart Citations